Sensuous atmospheres of landscape and memory (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Atmospheres are affective, sensory realms, where mood is palpable. Memory landscapes intensify affectivity, amplifying emotion. The senses, especially smell and taste, trigger and heighten memory. There is therefore a potent intersection between landscape, atmospheres, memory, and the senses. These connections present the compelling prospect that atmospheres could be designed, with the intention of enhancing memory landscapes through sensory means. This paper is written from the perspective of landscape architecture, a discipline which designs and shapes landscapes. Landscape architects work within the spatially and temporally fluid context of the landscape, and aligned with this is the prospect of generating and tuning atmospheres. Past traumatic events, losses of people and places, float in atmospheres of melancholy. Two projects are explored here to probe the possibilities of intentionally invoking atmospheres, exploring how the landscape could be sensorially tonalised. The memorial landscape of Pike River where 29 men died in a mine explosion, and Laura Daly’s augmented reality artwork, The Storm Cone, offer insights into the possibilities of atmospheric design.